2007
DOI: 10.1111/j.1524-4725.2007.33089.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bowen's Disease with Topical 5% Imiquimod Cream: Retrospective Study

Abstract: Topical 5% imiquimod cream appears to be clinically beneficial in the treatment of Bowen's disease and should be considered as a treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…The largest study available evaluated 49 patients and reported a clearance rate of 86% (42/49) after a once‐daily regimen for a mean of 9 weeks, with no recurrences after an average of 19 months of follow‐up 54 . Two smaller studies each used a regimen of once‐daily application for 16 weeks with somewhat similar results.…”
Section: Topical Therapymentioning
confidence: 97%
“…The largest study available evaluated 49 patients and reported a clearance rate of 86% (42/49) after a once‐daily regimen for a mean of 9 weeks, with no recurrences after an average of 19 months of follow‐up 54 . Two smaller studies each used a regimen of once‐daily application for 16 weeks with somewhat similar results.…”
Section: Topical Therapymentioning
confidence: 97%
“…51 Another study from Brazil reported that only 57% of patients (four of seven) with SCC in situ, without any significant comorbidities such as immunosuppression, cleared following a mean of 6Á1 weeks of treatment. 52 Single cases or small case series suggest that different regimens such as cyclical treatment 53 might be useful, and also that imiquimod might be effective for large facial lesions.…”
Section: Imiquimod (Strength Of Recommendation B; Level Of Evidence 1+)mentioning
confidence: 99%
“…It has been shown to be effective in treating PD of the scrotum 28,35 , vulva 36 , perianal region 35,37 , thigh 38 , and suprapubic region.39 Several prospective and retrospective studies have reported the efficacy of imiquimod and 5-FU in treating BD. 29,31,32,40 Based upon these promising results, several authors 30,37,40 have suggested that pharmacologic therapies be considered as an alternative to the surgical treatment of PD and BD. Results from our study support this contention by demonstrating the adverse impact of surgery on the long-term function of patients.…”
Section: Discussionmentioning
confidence: 98%